Komunikasi Transendental Perspektif Psikologi Kognitif - Neni Efrita (Universitas Islam Negeri Imam Bonjol Padang, 2010)
Transcendental Communications is the communication that goes on within ourselves and something outside the self and its existence was recognized by the individual. From this definition can be understood that the communication transendeltal means of communication within and outside the self that is intrapersonal. But who is outside of yourself that? Does God, jinns, angels, demons or all four? In the Islamic view of God, jinns, angels, and demons are supernatural. All Muslims must believe-Him because of the supernatural exists. “Allah swt” is the supernatural, angels, jinns and evil magic. The Most Invisible is a supernatural creator that is God Almighty